Simulain dulambayan ng manggagawa sa konteksto ng militanteng kilusang unyonismo (1980-1994) - Chua, Apolonio Bayani 1950- (University of the Philippines Press, 2009)
This book chronicles the evolution of workers' theatre groups within the trade unions from the founding of the first theatre group Tanghalang Silangan during the 1980s until the most expansive unification of Manila-based workers' theatre groups in 1994. More than just the history of trade unions, this study details the growth of street parliamentarians as regards their artistic expression and maturity.